In vitro and in vivo anti-snake venom (Daboia russelli) studies on various leaf extracts of Acalypha indica Linn. - K. Rajendran; Annie Shirwaikar; Maneesh Mehta; R. Vijaya Bharathi (International Journal of Phytomedicine, 2010)
The study aims to examine the Daboia russelli venom neutralization potential of the various leaf extracts of Acalypha indica (Euphorbiaceae) by in vitro and in vivo antisnake venom studies. In vitro HRBC membrane stabilization properties of these extracts at concentrations ranging from 2-400 μg/ml revealed inhibition of haemolysis induced by Russell’s viper venom, in a concentration dependent manner. The neutralizing potency of different leaf extracts viz., petroleum ether, benzene, chloroform and acetone extracts of Acalypha indica prepared by successive solvent extraction at intraperitoneal dose levels of 250, 500 and 750 mg/kg revealed that the acetone extract possessed the most significant activity on venom-induced lethality.